Symposium 7: Contributing to a Learning Methodology for Web 2.0 Learning: Identifying Central Tensions in Educational Use of web 2.0 Technologies - Glud, Louise Nørgaard; Buus, Lillian; Ryberg, Thomas; Georgsen, Marianne; Davidsen, Jacob (Proceedings of the International Conference on Networked Learning, 2010)
This paper contributes to the development of a methodology for designing Web 2.0 mediated learning based on a PBL approach. It does so by identifying tensions in the cross field between learning and Web 2.0. To establish an overview we begin by defining the intersections between learning and Web 2.0. In relation to this, and with reference to (Ryberg, Glud, Buus, & Georgsen, 2010), we argue that a problem-based approach to learning fits well with the characteristics of Web 2.0 activities. Moreover, we argue that the connection between Web 2.0 and learning gives rise to an overarching tension between who controls the networked learning environment and processes: the teacher or the learner? We propose a conceptual model where this tension can be understood as expressible across at least four dimensions: the learning process, the motivation, the infrastructure, and resources/content. Also we identify a number of crucial questions that need to be considered in relation to each of these dimensions when designing for web 2.0 mediated learning. These questions and tensions are what we explore in this paper as they contribute to the development of a learning methodology and some mediating design artefacts, which we further discuss in (Buus, Georgsen, Ryberg, Glud, & Davidsen, 2010). The intention of the conceptual model and questions is to prompt practitioners to discuss and critically reflect on their course designs during the planning and design phase. Furthermore, we discuss some additional mediating design artefacts, which we are developing to support practitioners’ design of Web 2.0 oriented learning. These are descriptions of existing practices and activities which will be uploaded in the wiki-based social community Methopedia.